Co‐owned Local Government Organisations: Conditions for Strategy Development. (August 2015) - Mattisson, Ola; Ramberg, Ulf
Abstract Local governments tend to join resources and create co‐owned organisations to solve the supply of public services. From a strategic perspective on local government cooperation, this paper analyses the conditions for strategy development in a co‐owned municipal organisation. The empirical data stem from a longitudinal case study of a Swedish provider of water and sewerage services. We show that difficulties in formulating and agreeing upon strategies are not dependent on the structural form. Instead, there is an intrinsic dilemma when municipalities are to create a joint strategy at the same time as each municipality is sovereign to decide on all local matters.